Aplikasi Sistem Informasi Administrasi Dan Inventori Berbasis Website Pada Toko Sumber Mulia - Renardi Dewanto Cahyadi; Agustinus Noertjahyana; Kartika Gunadi (Jurnal Infra, 2016)
Toko Sumber Mulia is a commercial enterprise engaged in the sale of daily necessities (groceries) located at Jl. Iskandar Pertokoan Blok 10 no.2 Sampit - Central Kalimantan. The trading business requires administrative information systems that can be expected to process administrative records and stock will be easier to do and can saving time. The use of the web on the information system to function so that the owner can control the shop with ease even though you are not in the store by using a personal computer.This application is made by using PHP and MySQL Server as the database storage system. The method used in the calculation of cost of sales is by using the FIFO (First In First Out).From the results of testing of applications, indicates that the application can process data directly related to the process of buying and selling automatically. Sales report, purchase report, stock reports and income statement can be done quickly.